Dampak Penyaluran Bantuan Sosial Tunai Pandemi Covid-19 (Studi Kasus di Kelurahan Sikumana – Kota Kupang) - Muga, Maria Prudensiana Leda; Kiak, Novi Theresia; Maak, Clarce Sarliana (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2021)
This study aims to determine the management of Cash Social Assistance in Sikumana Village, in addition to knowing more about the impact of cash social assistance (BST) on communities affected by Covid-19 in Sikumana Village. The research method used descriptive qualitative method. The results obtained from this study indicate that the management of COVID-19 assistance in the Sikumana Village is not optimal, socialization is needed about the benefits of the assistance, so that the community has awareness of the importance of self-data reporting, so that data duplication does not occur. in the village.